Utilization of Plastic Bottle Waste as a Vertical Garden Media in the Dense Population Area of ​​Binjai Village, Binjai District, Binjai City - Naria, Evi; Arde, Lanova Dwi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
One of the characteristics of a healthy environment is properly waste managed. Densely populated are areas where waste management needs to be improved. Plastic bottle is one type of waste that is widely available in densely populated areas. This waste, is difficult to decompose in the environment, and has not been managed optimally. The use of plastic bottle needs to be reduce the problem of waste, among others, it can be used as a vertical garden media. The methods are discourse, discussions, demonstrations, and practice how to create the plastic bottles make to vertical garden media. The participants are non-productive people, they are housewives. An important result of the activity is that the participants have the understand, skills and ability to make a vertical garden independently. Plastic bottle waste becomes useful, no longer becomes garbage. Plastic bottles are a growing media for vegetable and medicinal plants, that can beautify and green the environment in densely populated areas. It is hoped that participants will develop their potential in managing the environment starting from home, and sharing skills with the surrounding community.